Cara Pandang dan Upaya Pemerintah Dalam Mengurangi Kemiskinan - Umami, Ulfatul (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Poverty is a complex and multidimensional phenomenon that has been faced by Indonesia since before independence. Therefore, the Indonesian government is committed to reduce the poor in accordance with the established in the MDGs. The availability of valid and up to date data is required to implement effective poverty reduction policies. There are two agencies that collect poverty data in Indonesia, i.e. BPS and BKKBN. The purposes of this study are to determine the government's perspective in measuring poverty and to identify the poverty alleviation programs that have been done. Through documents analysis, data exploration, as well as extracting information from several sources, can be concluded that the government's vision on poverty is influenced by the goals and interests of each institution. In the implementation of the program, such as the distribution of Raskin in Blitar, East Java, accuracy and validity data of the target still become a constraint. Somehow it is also influenced by the differences of existing data. Thus, it needs a good synergy between institutions to produce quality data, so that the goal of poverty reduction can be achieved.